MANAGEMENT APPLICATION FOR MOBILE DEVICES: proposal for implementation in a school center - Vercesi, Heloisa Camara; Bruno, Diego Renan (Revista Interface Tecnológica, 2023)
With the significant growth in the use of mobile devices and the strengthening of online buying and selling, companies invest in technologies to keep up with market demands using applications, social networks and the internet in order to increase profits and keep up to date. Given this scenario, the proposal to implement an application for mobile devices with the objective of managing a school canteen is gaining space in the sector, obtaining advantages of quickly placing orders, ease of viewing products and prices, making payments and managing control of sales, ordering and inventory management. Therefore, information security is of paramount importance in order to obtain measures and practices to protect confidential data from customers and employees. A survey was carried out in a school regarding the use of the application for orders in the canteen in order to evaluate the purpose of this article.
Keywords: application; mobile devices; school canteen